Assessment of whether in-hospital mortality for lobectomy is a useful standard for the quality of lung cancer surgery: retrospective study. Issue 7406 (10th July 2003) - Treasure, Tom; Utley, Martin; Bailey, Alan
Abstract : Objectives To calculate in-hospital mortality after lobectomy for primary lung cancer in the United Kingdom; to explore the validity of using such data to assess the quality of UK thoracic surgeons; and to investigate the relation between in-hospital mortality and the number of procedures performed by surgeons. Design Retrospective study. Setting 36 departments dealing with thoracic surgery in UK hospitals. Participants 4028 patients who had undergone lobectomy for primary lung cancer by one of 102 surgeons. Main outcome measures In-hospital mortality in relation to individual surgeons, among all patients, and among each of five groups of patients defined by the number of operations performed by the surgeon. Results 103 patients (2.6%, 95% confidence interval 2.1% to 3.1%) died after surgery during the same hospital admission. No significant difference was found for in-hospital mortality between the five groups. Conclusions The number of procedures performed by a thoracic surgeon is not related to in-hospital mortality. Reporting data on in-hospital mortality after lobectomy for primary lung cancer is a poor tool for measuring a surgeon's performance.